(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Hybrid wind-wave systems, which integrate floating offshore wind turbines with wave energy converters, have emerged as a promising solution for enhancing the stability and energy efficiency of offshore renewable platforms. This review explores recent advances in the use of wave energy converters and control strategies aimed at improving platform motion suppression, structural load mitigation, and power production within hybrid wind-wave systems. Particular emphasis is placed on the dynamic coupling between wind and wave subsystems, with a focus on co-optimised control approaches that leverage the power take-off of wave energy converters to support traditional wind turbine control mechanisms. The review includes an overview of classical wind turbine control, passive damping techniques such as tuned mass dampers, and recent methodologies that combine conventional wind turbine controllers with power take-off control systems. Additionally, a comparative summary of typical hybrid wind-wave systems topologies and control architectures is presented.